Customised pediatric palliative care: Integrating oncological and palliative care priorities. (17th September 2020) - Podda, Marta; Schiavello, Elisabetta; Visconti, Giovanna; Clerici, Carlo Alfredo; Armiraglio, Mariangela; Casiraghi, Giovanna; Ambroset, Sonia; Grossi, Alberto; Rizzi, Barbara; Lonati, Giada; Massimino, Maura
Abstract: Aim: To describe the experience involving the early introduction of palliative care (PC) in oncological patients treated within the paediatric oncology unit of the Istituto Nazionale Tumori of Milan and compare this cohort with a cohort of patients resident in the same area treated before the introduction of early palliative care. Methods: A virtual team was assembled in 2015. The PC providers operate outside the hospital. Conference calls were scheduled to discuss patients' problems. This sample was compared with the clinical records of patients residing in the same area who died between 2009 and 2014. Results: Between January 2015 and April 2019, 41 patients residing in the Milan area mainly with CNS tumours or sarcomas were referred to the team. Comparing the results with the previous cohort, there was a rise in the number of patients dying at home or in a hospice and the duration of PC increased over time. From 2015, none of the patients died in an intensive care unit. Conclusion: Patients managed by the virtual team were able to continue their cancer treatments, take part in Phase I trials and receive PC. All patients with a poor prognosis should have PC at an early stage.